External Urethral Sphincter Motoneuron Properties in Adult Female Rats Studied In Vitro - Carp, Jonathan S. (American Physiological Society, 2010)
The external urethral sphincter (EUS) muscle plays a crucial role in lower urinary tract function: its activation helps maintain continence, whereas its relaxation contributes to micturition. To determine how the intrinsic properties of its motoneurons contribute to its physiological function, we have obtained intracellular current-clamp recordings from 49 EUS motoneurons in acutely isolated spinal cord slices from adult female rats. In all, 45% of EUS motoneurons fired spontaneously and steadily (average rate = 12–27 pulses/s). EUS motoneurons were highly excitable, having lower rheobase, higher input resistance, and smaller threshold depolarization than those of rat hindlimb motoneurons recorded in vitro. Correlations between these properties and afterhyperpolarization half-decay time are consistent with EUS motoneurons having characteristics of both fast and slow motor unit types. EUS motoneurons with a slow-like spectrum of properties exhibited spontaneous firing more often than those with fast-like characteristics. During triangular current ramp-induced repetitive firing, recruitment typically occurred at lower current levels than those at derecruitment, although the opposite pattern occurred in 10% of EUS motoneurons. This percentage was likely underestimated due to firing rate adaptation. These findings are consistent with the presence of a basal level of persistent inward current (PIC) in at least some EUS motoneurons. The low EUS motoneuron current and voltage thresholds make them readily recruitable, rendering them well suited to their physiological role in continence. The expression of firing behaviors consistent with PIC activation in this highly reduced preparation raises the possibility that in the intact animal, PICs contribute to urinary function not only through neuromodulator-dependent but also through neuromodulator-independent mechanisms.